2014
DOI: 10.1038/nrneurol.2014.207
|View full text |Cite
|
Sign up to set email alerts
|

Microglial and macrophage polarization—new prospects for brain repair

Abstract: The historical view of the adult brain as a static organ has shifted in the last few decades. We now know that the mature brain remains plastic and has some regeneration capacity after injury. The injured brain engages microglia/macrophages to clear cellular debris and fine-tune neurorestorative processes. However, microglia/macrophage activation can also hinder central nervous system (CNS) repair and expand tissue damage. One explanation for this dualistic role of microglia/macrophages in neurological recover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
1,025
2
13

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,168 publications
(1,053 citation statements)
references
References 117 publications
13
1,025
2
13
Order By: Relevance
“…However, we report that CD40 + microglia and macrophages are highest 24–48 hr after stroke and decrease by 1 week post‐stroke. Using different rodent models that result in varying degrees of lesion severity may explain the difference between this study and previous studies since the temporal profile of microglia and macrophage infiltration varies widely depending on stroke severity (Hu et al., 2015). Additionally, inflammation peaks 24–72 hr after ischemic stroke, and our data support this with increased CD40 + macrophages at these time points.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we report that CD40 + microglia and macrophages are highest 24–48 hr after stroke and decrease by 1 week post‐stroke. Using different rodent models that result in varying degrees of lesion severity may explain the difference between this study and previous studies since the temporal profile of microglia and macrophage infiltration varies widely depending on stroke severity (Hu et al., 2015). Additionally, inflammation peaks 24–72 hr after ischemic stroke, and our data support this with increased CD40 + macrophages at these time points.…”
Section: Discussionmentioning
confidence: 99%
“…Activation of microglia and macrophages by IL‐4, IL‐10, or tumor growth factor (TGF)β induces the M2 state, which is characterized by wound repair, debris clearance, and the release of anti‐inflammatory cytokines (Martinez & Gordon, 2014; Stein, Keshav, Harris, & Gordon, 1992). These opposing phenotypes play an important role in neuroinflammation and it is hypothesized that altering the activation of microglia and macrophages from the M1 side of the spectrum to the M2 side could be beneficial in ischemic stroke (Hu et al., 2012, 2015; Yenari, Kauppinen, & Swanson, 2010). …”
Section: Introductionmentioning
confidence: 99%
“…In contrast, microglia could change to the alternative anti-inflammatory M2 profile owing to the effects of the cytokines IL-4 and IL-13 [15]. M2 microglial cells expressed higher levels of arginase I (ArgI) and folate receptor 2 (FOLR2), and synthesize and release anti-inflammatory cytokines such as IL-10 and transforming growth factor (TGF)-β [16,17]. The enhancement of the M2 profile affords neuroprotection in some neuropathological conditions and its role in neuropsychiatric diseases is currently emerging [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The proinflammatory M1 phenotype favors the production and release of cytokines that exacerbate neural injury (18,19). In contrast, the M2 phenotype promotes the release of neurotrophic factors that promote neurorepair (18,20). We recently showed that M1 conditioned medium (CM) enhances oligodendrocyte cell death in vitro following oxygen glucose deprivation (OGD), whereas M2 CM is protective (19,21).…”
mentioning
confidence: 99%